Formulation & evaluation of colon targeted drug delivery system of omeprazole - P.Vinay Kumar; Ganesh kumar Gudas (International Journal of Pharmacy and Analytical Research, 2022)
The purpose of the present study was to formulate colon delivery tablets of Omeprazole, an Anti-ulcer agents. Omeprazole tablets were prepared by direct compression method employing rate controlling the synthetic polymer Eudragit RSPO, Eudragit RLPO The Prepared granules were subjected for pre compressional and drug excipient compatibility studies and tablets were evaluated for post compressional parameters such as weight variation, hardness, friability, drug content, and Invitro dissolution studies. It was concluded that the out of all the formulations F12 was the best formulation as the extent of drug release was found to be 96 % upto 24 hrs and the kinetics of drug release was follows first order kinetics with the „n‟ value of more than 0.5 indicates that non-fickian mechanism. % Cumulative drug release from all the prepared formulation was found to be in following order F12>F11>F10>F9>F8>F7>F6>F5>F4>F3>F2>F1 The kinetics of optimized formulation F12 was found to be follows first order kinetics and the „n‟ is more than 0.5 indicates that it follows non-fickian mechanism. Endured super case II release, during the dissolution study, which indicated that polymer relaxation, had a significant role in the drug release mechanism. Drug release mechanism was case II non-Fickian (anomalous) release (0.5≤ n ≤ 0.89).